Schizophrenia - Smith, Douglas W. (Douglas Wayne), 1949- (New York : F. Watts, 1993)
Describes the nature, causes, and treatment of this common type of mental illness.
Includes bibliographical references (p. 92) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Schizophrenia -- Juvenile literature; Mental illness; Schizophrenia; Mental illness; Schizophrenia